Behavioural adaptation of crossbred cows in automatic concentrate feeding station - PRAKASH, MANI ARUL; PRASAD, SHIV; MOHANTY, TUSHAR KUMAR; KUMARESAN, ARUMUGAM; MANIMARAN, AYYASAMY; OBEROI, PARVENDER SINGH; LAYEK, SIDDHARTHA SHANKAR; LATHIKA, SREELA (The Indian Journal of Animal Sciences, 2018)
The present study evaluated the adaptation behaviour of crossbred cows (46) in Automatic Concentrate Feeding Station (ACFS). The adaptation behaviour was studied over a period of 6 weeks. The percentage of adaptation was calculated based on the average concentrate allotted divided by average number of rewarded visits. After adaptation, duration of rewarded and unrewarded visits under three feeding windows (FW1: 12.01 AM - 7.59 AM; FW2: 8.00 AM - 3.59 PM; FW3: 4.00 PM -11.59 PM) in 2 ACFS (FS1 & FS2) was studied over a period of 72 h using software. Significant difference in the duration of rewarded visits was observed between stations (FS1 and FS2) and between feeding windows (FW1 and FW3 differed with FW2). The average duration of rewarded visit was 247.3±7.97 sec, 192.46±7.29 sec and 239.47±8.21 sec during FW1, FW2 and FW3, respectively, while the corresponding values for unrewarded visits were 44.49±3.77 sec, 46.73±2.9 sec and 59.84±3.32 sec, respectively. Overall mean duration of time spent for a single visit in rewarded and unrewarded visits was 218.56±3.82 sec and 49.93±1.85 sec, respectively, for 72 h irrespective of feeding stations and feeding windows. It was concluded that adaptation period of crossbred cows with automatic concentrate feeding station was shorter for older animals than younger ones, and the duration of unrewarded visits influenced the learning behaviour of animals.